Effect of staphylokinase-derived nonadecapeptide on the activation of plasminogen - Okada, Kiyotaka; Ueshima, Shigeru; Matsuno, Hiroyuki; Kawao, Naoyuki; Okamoto, Chikako; Tanaka, Masaki; Matsuo, Osamu (Thrombosis and Haemostasis, 2007)
Staphylokinase (SAK) expresses plasminogen activator (PA) activity by forming a complex with plasmin. The interaction between the plasmin-SAK complex and plasminogen was investigated using synthesized peptides, which were constructed according to the amino acid sequence of the SAK molecule.A synthetic nonadecapeptide (SAK22–40) corresponding to Glu22-Leu40 by the SAK molecule enhanced the activation of Glu-plasminogen by the plasmin-SAK complex.Analysis of IAsys resonant mirror biosensor showed that SAK22–40 bound to Glu-plasminogen.This binding was completely inhibited by IgG against the B-chain in the plasminogen molecule. But, this binding was not inhibited by IgG against lysine-binding sites (LBS) of the A-chain in the plasminogen molecule. The substitution of Lys35 with Ala in SAK22–40 did not enhance the activation of Glu-plasminogen by the plasmin-SAK complex. When SAK22–40 was administrated in a mouse thrombosis model, earlier recanalization was observed than in mice with vehicle administration. Thus, a newly synthesized peptide, SAK22–40 enhanced Glu-plasminogen activation and induced effective thrombolysis.
Keywords: Staphylokinase; plasminogen; synthetic peptide; plasminogen activation; thrombolysis